Temporal Dynamics of Ocular Position Dependence of the Initial Human Vestibulo-ocular Reflex - Crane, Benjamin T; Tian, Junru; Demer, Joseph L (Investigative ophthalmology & visual science, 2006)
While an ideal vestibulo-ocular reflex (VOR) generates ocular rotations compensatory for head motion, during visually guided movements, Listing's Law (LL) constrains the eye to rotational axes lying in Listing's Plane (LP). The present study was conducted to explore the recent proposal that the VOR's rotational axis is not collinear with the head's, but rather follows a time-dependent strategy intermediate between LL and an ideal VOR. Binocular LPs were defined during visual fixation in eight normal humans. The VOR was evoked by a highly repeatable transient whole-body yaw rotation in darkness at a peak acceleration of 2800 deg/s2. Immediately before rotation, subjects regarded targets 15 or 500 cm distant located at eye level, 20 degrees up, or 20 degrees down. Eye and head responses were compared with LL predictions in the position and velocity domains. LP orientation varied both among subjects and between individual subject's eyes, and rotated temporally with convergence by 5 +/- 5 degrees (+/-SEM). In the position domain, the eye compensated for head displacement even when the head rotated out of LP. Even within the first 20 ms from onset of head rotation, the ocular velocity axis tilted relative to the head axis by 30% +/- 8% of vertical gaze position. Saccades increased this tilt. Regardless of vertical gaze position, the ocular rotation axis tilted backward 4 degrees farther in abduction than in adduction. There was also a binocular vertical eye velocity transient and lateral tilt of the ocular axis. These disconjugate, short-latency axis perturbations appear intrinsic to the VOR and may have neural or mechanical origins.